The relationship between progesterone and Th-related cytokines in plasma during early pregnancy in cows - CHENG, Lei; XIN, Youdong; LIU, Xiaohua; HU, Xiuzhong; XIANG, Min; WANG, Dingfa; ZHAO, Shuhong (Frontiers of Agricultural Science and Engineering, 2016)
In cows,progesterone(P4) is essential for the maintenance of pregnancy and successful embryo development is dependent on the maternal immunomodulation of Th-related cytokines.However,in vivo investigation of the relationship between P4 and Th immunity in cattle remains incomplete.Therefore,we evaluated plasma P4 concentrations and expressions of three Th-related cytokines,interleukins IL-1β,IL-4 and IL-6,in 15 pregnant and 11 non-pregnant cows 0,14,18,21,and28 d post artificial insemination.Pregnant cows had significantly higher plasma P4 levels and pregnant cows with higher P4 on 14 d tended to have higher P4 in the subsequent period of pregnancy.There was no difference in IL-4 and IL-6 expression between pregnant cows and non-pregnant cows,whereas plasma IL-1β was temporally upregulated on 21 d.The cytokines measured were not affected in either the high-P4 group( > 11.1 ng·m L–1) or the low-P4 group( < 11.1 ng·m L–1) in pregnant cows.A weak negative correlation between IL-1β and IL-6 was observed,but none of the cytokines was associated with a change in plasma P4.In conclusion,there was no clear relationship between P4 and Th immunity in maternal plasma in the pregnant cows,which differs from what occurs in humans and mice during early pregnancy.